2012
DOI: 10.1371/journal.pone.0035549
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Portrait of Actinobacillus pleuropneumoniae during Acute Disease - Potential Strategies for Survival and Persistence in the Host

Abstract: BackgroundGene expression profiles of bacteria in their natural hosts can provide novel insight into the host-pathogen interactions and molecular determinants of bacterial infections. In the present study, the transcriptional profile of the porcine lung pathogen Actinobacillus pleuropneumoniae was monitored during the acute phase of infection in its natural host.Methodology/Principal FindingsBacterial expression profiles of A. pleuropneumoniae isolated from lung lesions of 25 infected pigs were compared in sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 97 publications
4
29
1
Order By: Relevance
“…This result is in accordance with a previous study, which showed that the type IV fimbrial promoter is induced upon contact with host cells via the luxAB reporter system (22). Besides, two recent studies that looked at A. pleuropneumoniae gene expression during natural and experimental infections in pigs also indicated the upregulation of genes coding for type IV fimbriae (36,37).…”
Section: Figsupporting
confidence: 92%
“…This result is in accordance with a previous study, which showed that the type IV fimbrial promoter is induced upon contact with host cells via the luxAB reporter system (22). Besides, two recent studies that looked at A. pleuropneumoniae gene expression during natural and experimental infections in pigs also indicated the upregulation of genes coding for type IV fimbriae (36,37).…”
Section: Figsupporting
confidence: 92%
“…To identify genes that might be involved in host-pathogen interactions and biofilm formation, transcriptomes from this study were cross-referenced with previous transcriptional study performed by our and other laboratories [19,21,38]. The drip-flow biofilm was the condition that shared the most genes with a natural infection analysis (20 genes; Table 3; [21]) and an experimental infection analysis (13 genes; Table 3; [38]).…”
Section: Resultsmentioning
confidence: 99%
“…The drip-flow biofilm was the condition that shared the most genes with a natural infection analysis (20 genes; Table 3; [21]) and an experimental infection analysis (13 genes; Table 3; [38]). The 4h-static biofilm and the 6h-static biofilm shared 4 and 14 genes with the natural infection analysis and shared 4 and 8 genes with the experimental infection analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We used aerobiosis as it is the typical atmosphere used in experiments involving A. pleuropneumoniae and anaerobiosis as, based on mutant Jacobsen et al 2005;Buettner et al 2009) or transcriptome (Deslandes et al 2010;Klitgaard et al 2012) studies, it is representative of the growth conditions found in necrotic lungs of pigs. As shown in Figure 4 and Table 1, some trans-acting sRNA candidates, like Arrc05 and Arrc08, are located between genes within operons, which could allow them to be mistaken for subproducts of polycistronic mRNA maturation.…”
Section: Discussionmentioning
confidence: 99%